THE IMPLEMENTATION OF TRANSLANGUAGING IN EFL LISTENING CLASSROOM: STUDENTS’ VOICES - Siti Kayla Almira Minerva; Muhammad Handi Gunawan (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
Nowadays, there are numerous studies on translanguaging in various contexts. However, there remains a notable gap in studies specifically examining the application of translanguaging in the context of listening in the classroom. To fill this gap, this study examines how students perceive the application of translanguaging in an EFL listening classroom at a public university in Indonesia. Translanguaging, as a multilingual pedagogical approach, allows students to utilize both their first language (L1) and the target language (L2) to enhance their comprehension and participation in an English as a Foreign Language (EFL) classroom. Using a qualitative case study methodology, the data were collected through classroom observations, open-ended questionnaires, and semi-structured interviews.  The findings revealed that translanguaging offers significant benefits, including improved students' understanding of complex material, increased students' confidence in expressing ideas, and created a more interactive learning environment. However, some challenges also arise and are faced by the students, such as the over-reliance on L1 and the limitation of English skills improvement. Despite these challenges, the study emphasizes the importance of a balanced approach to translanguaging, enabling students to utilize their linguistic skills while at the same time improving their English proficiency. These insights add to the ongoing research on integrating translanguaging in EFL contexts to support diverse learner needs.